Radio-loudness in black hole transients: evidence for an inclination effect. Issue 4 (2nd June 2018) - Motta, S E; Casella, P; Fender, R P
ABSTRACT: Accreting stellar-mass black holes appear to populate two branches in a radio:X-ray luminosity plane. We have investigated the X-ray variability properties of a large number of black hole low-mass X-ray binaries, with the aim of unveiling the physical reasons underlying the radio-loud/radio-quiet nature of these sources, in the context of the known accretion–ejection connection. A reconsideration of the available radio and X-ray data from a sample of black hole X-ray binaries confirms that being radio-quiet is the more normal mode of behaviour for black hole binaries. In the light of this we chose to test, once more, the hypothesis that radio-loudness could be a consequence of the inclination of the X-ray binary. We compared the slope of the 'hard-line' (an approximately linear correlation between X-ray count rate and rms variability, visible in the hard states of active black holes), the orbital inclination, and the radio-nature of the sources of our sample. We found that high-inclination objects show steeper hard-lines than low-inclination objects, and tend to display a radio-quiet nature (with the only exception of V404 Cyg), as opposed to low-inclination objects, which appear to be radio-loud(er). While in need of further confirmation, our results suggest that – contrary to what has been believed for years – the radio-loud/quiet nature of black-hole low-mass X-ray binaries might be an inclination effect, rather than an intrinsic source property. This would solve an important issue in the context of the inflow–outflow connection, thus providing significant constraints to the models for the launch of hard-state compact jets.